Determining prehistoric skin processing technologies : the macro and microscopic characteristics of experimental samples - Kamper, Theresa Emmerich (Sidestone Press, 2020)
The importance of skin processing technologies in the history and expansion of humankind cannot be overstated, yet these technologies can be difficult to identify in the archaeological record. This research outlines the development of a systematic, non-destructive method for identifying the tanning technologies used to produce prehistoric skin artefacts. The approach combines extensive archaeological research and over 25 years of the author's personal tanning experience. The method employs observations of an extensive sample reference collection, both macroscopic and microscopic, to produce a database of defining characteristics for six tannage types, from a large geographic area and time frame.